Smart Infotainment System for Vehicular Network - Siddharthraju, K; Dhivya Devi, R; Shanmugaraja, T; Mithunraj, S; Sophia, S (International Journal of Engineering and Technology, 2018)
On fast moving life, time management has become an important factor. Objective of this paper is to implement features of high range vehicles even in middle range vehicles through few performance metric improvements. The parametric and non-parametric analysis is applied to evaluate vibration modes. In a Vehicular Ad hoc Network (VANET), vehicles communicate with each other through Dedicated Short-Range Communication (DSRC) wireless devices. Equipped with hundreds of smart sensors, vehicles can detect their own parameters (such as braking, lane changes, and acceleration) and road conditions (such as icy roads and weather conditions).Vehicular ad hoc networks, the spontaneous creation of a wireless network for data exchanges, are used for clustering data. Quantitative data analysis is carried out for decision making.Â